هل سيغير الأتفاق النووي الأيراني من جيوبوليتيكية الشرق الأوسط ؟ (مجلة تكريت للعلوم السياسية, 2017)
As the September 17, 2015 deadline set by the U.S. Congress for the implementation of the Iranian nuclear deal (JCPOA) approached, the media was flooded with headlines, comments, and blog posts, presenting arguments both for and against the agreement. Those who supported the deal, despite considering it flawed, argued that it was the best deal that could be reached through intrusive inspections, which would ensure that Iran's nuclear program remains peaceful and does not achieve its goal of acquiring nuclear weapons. On the other hand, opponents of the deal put forth arguments such as "Iran is an untrustworthy partner, and we prefer sanctions," "Iran should not possess any nuclear capability," "Iran is an enemy of Israel," and "The agreement will only last for fifteen years." It appears that both sides in this debate agree that this agreement will fundamentally change the geopolitical reality of the Middle East. But is this really true?Please note that this translation is based on the information you provided, and it may not capture all the nuances and complexities of the original text.
Keywords: الاتفاق النووي الأيراني; الشرق الأوسط